Relationship between the dimensions of senior subject teachers’ (GKMP) instructional leadership and the learning organisation at schools - Abas, Nurnazahiah; Basri, Ramli (Malaysia Association of Research and Education for Educators, 2019)
Generally, education is aimed at ensuring that every student is provided with the knowledge, skills and values to succeed in future life. In Malaysia and around the world, awareness of the importance of change in education towards ensuring our country remains globally competitive, has to take place in parallel with the post-industrial IR 4.0 era. Flexible human capital requirements necessitate a change in the education system. Accordingly, schools as a learning organisation is a concept that was firstly examined by researchers and school leaders in the field of education. Schools that show improvements in performance are schools where not only aretheir students learning, but all of the school’s staff are constantly learning and improving work practices for excellence. One of the catalytic factors for change in school is instructional leadership. The focus of this study is to examine the relationship between the dimensions of instructional leadership practice by senior subject teachers with learning organisations at secondary schools. This study uses as instrument adapted from the Principal Instructional Management Rating Scale questionnaire, PIMRS by Halinger(2000) and modification of instrument by Zamzam (1999) to measure instructional leadership of senior subject teachers. Learning organisation was measured by Learning Dimension of Learning Organizational Questionnaire (DLOQ) built by Watkins and Marsick (1996).The findings show that the instructional leadership of senior subject teachers has a significant correlation to the learning organisation in school. This means that when the instructional leadership of senior subject teachers increases, the learning organisation in the school also increases. Improved practice of instructional leadership by senior subject teachers in all three dimensions which are defining school missions, managing teaching programmes and creating a positive learning environment can enhance the practice of learning organisation. In line with this finding, GKMP should always be clear and understand the vision and mission of the school as well, and together with its team members from various departments, establish their respective vision and mission that are consistent with the school’s. Senior subject teacher should also act as mentors to team members in guiding the implementation of best practices in the learning process in the classroom and thus promoting collaboration in teams. Most importantly, senior subject teachers should be able to create a positive learning environment to improve the practice of learning organisation at schools.